Perlindungan Baja Ringan Dalam Medium Asam Klorida Menggunakan Ekstrak Daun Sungkai (Peronema canescens Jack) - Stiadi, Yeni; Emriadi; Rahmayeni; Yolanda, Putri; Della Rosalynna S. (Jurnal Kimia Unand, 2024)
Corrosion inhibition of mild steel in 1 M hydrochloric acid (HCl) by leaves extract of sungkai (Peronema canescens Jack) was studied by weight loss method, Fourier Transform Infra-Red (FTIR), spectroscopy UV-Vis, and optical microscopy. The corrosion rate of mild steel increase with the increase of temperature and decrease with the increase of concentration from leaves extract of sungkai in medium. The weight loss method shows that the inhibition efficiency increased with concentration and increases with temperature increase. The highest inhibition efficiency was 90.70% with the addition of 10 g/L extracts at 60ºC. The adsorption of the inhibitor on the surface of mild steel follows the Langmuir adsorption isotherm because it forms a monolayer. Analysis of FTIR and UV-vis spectroscopy showed an interaction between leaves extract of sungkai and mild steel surface. Optical microscopy analysis revealed differences in the surface of mild steel immersed in 1 M HCl medium with and without the addition of extract.